2013
DOI: 10.1111/bcpt.12090
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterisation of a Structurally Novel α2C ‐Adrenoceptor Antagonist ORM‐10921 and its Effects in Neuropsychiatric Models

Abstract: Abstract:The a 2 -adrenoceptors (ARs) are important modulators of a wide array of physiological responses. As only a few selective compounds for the three a 2 -AR subtypes (a 2A , a 2B and a 2C ) have been available, the pharmacological profile of a new a 2C -selective AR antagonist ORM-10921 is reported. Standard in vitro receptor assays and antagonism of a 2 , and a 1 -AR agonist -evoked responses in vivo were used to demonstrate the a 2C -AR selectivity for ORM-10921 which was tested in established behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 46 publications
8
45
2
Order By: Relevance
“…Its target optimization included D 2 partial agonism with low intrinsic activity, 5-HT 1A partial agonism, and antagonism at 5-HT 2A , a 1B -and a 2C -adrenergic receptors (Maeda et al, 2014), supporting a favorable antipsychotic profile with low EPS risk and potential to treat core symptoms in schizophrenia, including cognitive deficits (Arnt and Skarsfeldt, 1998;Drouin et al, 2002;Marcus et al, 2010;Newman-Tancredi and Kleven, 2011;Sallinen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its target optimization included D 2 partial agonism with low intrinsic activity, 5-HT 1A partial agonism, and antagonism at 5-HT 2A , a 1B -and a 2C -adrenergic receptors (Maeda et al, 2014), supporting a favorable antipsychotic profile with low EPS risk and potential to treat core symptoms in schizophrenia, including cognitive deficits (Arnt and Skarsfeldt, 1998;Drouin et al, 2002;Marcus et al, 2010;Newman-Tancredi and Kleven, 2011;Sallinen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been shown that the nonselective a 2 -adrenoceptor antagonist atipamezole (Blaxall et al, 1991) improves ID-ED-shift performance in naive rats (Lapiz and Morilak, 2006). Furthermore, the selective a 2C -antagonist ORM-10921 [(1S,12bS)-1-(methoxymethyl)-1-methyl-2,3,4,6,7,12b-hexahydro-1H-benzofuro[2,3-a]quinolizine] reverses cognitive deficits induced by acute treatment with MK-801 [dizocilpine, (5S,10R)-(1)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine] (Sallinen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All a 1 -adrenoceptor subtypes are coexpressed with 5-HT 2A receptors in frontal cortex, but their relative functional importance is unknown (Santana et al, 2013). Similarly, the a 2C -adrenoceptor field is immature, but antagonism has been proposed to contribute to antidepressant-like and procognitive activity (Quaglia et al, 2011;Sallinen et al, 2013). Clearly, more studies are necessary to explore the role of a-adrenoceptor antagonism for the profile of brexpiprazole.…”
Section: Brexpiprazole a Novel Serotonin-dopamine Activity Modulatormentioning
confidence: 99%
“…Accordingly, an optimized target profile may lead to improvements in both clinical efficacy and adverse effect profile in the treatment of schizophrenia. Furthermore, a broader pharmacological profile (e.g., on selected 5-HT receptors and a-adrenoceptor subtypes) could potentially provide opportunities for the treatment of a variety of other central nervous system (CNS) disorders and symptoms, such as depression and anxiety, as well as stress and impulse control disorders (Drouin et al, 2002;Roth et al, 2004;Arnt et al, 2008;Wong et al, 2008;Sallinen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there has been no selective PET tracer available for α 2C ‐ARs to be used in studies aiming to determine whether a novel α 2C ‐AR‐targeted drug candidate can gain access into the CNS and what doses and dosing intervals should be used in clinical trials. α 2C ‐ARs are potential targets in neuropsychiatric and neurodegenerative disorders, as they have been found to modulate the performance of experimental animals in tests predicting efficacy in depression and cognitive dysfunction (Sallinen et al, ; Scheinin et al, ). Several efficacious antipsychotics, most notably clozapine, have significant affinity for α 2C ‐ARs (Kalkman and Loetscher, ).…”
Section: Introductionmentioning
confidence: 99%